Rapid Identification of Candida albicans Septicemia in Man by Gas-Liquid Chromatography - Miller, Geraldine G. (1974)
Gas-liquid chromatography (GLC) was used to study normal serum and serum from patients with septicemia caused by a variety of bacteria and by Candida albicans. The gas chromatograms of seven sera from six patients with septicemia due to C. albicans were found to be significantly and reproducibly different from those of normal sera. Chromatograms of serum from 19 bacteremic patients were indistinguishable from normals. The major peaks present in chromatograms of normal sera were identified by GLC and mass spectroscopy as the methyl esters of palmitic, oleic, linoleic, and stearic acids. In addition to these peaks, serum from patients with candidemia contained abnormal peaks that were also present in cultures of C. albicans grown in normal serum and in washed C. albicans harvested from cultures in yeast nitrogen base broth. Chromatograms from 11 cases of mucosal candidates differed little from normal and were easily distinguished from those of fungemia patients. Chromatograms of serum from two of four patients with deep-invasive candidiasis were indistinguishable from those of fungemia and reverted to normal after infections were eradicated.